Recent advances in estimation of paraquat using various analytical techniques: A review - Rajendran Rajaram; Lakshman Neelakantan (Results in Chemistry, 2023)
Agriculture, one of the ancient occupations is considered as the backbone of any civilization across the countries. Development of agriculture and its technology has constantly evolved right from its origin. To increase agricultural productivity, people have started using pesticides. In ancient times, people used organic manures, however later, they have moved to synthetic/chemical pesticides, which are hazardous as well. The synthetic pesticides are not only harmful towards human beings but also to the environment. Among the available pesticides, paraquat (PQ) is one of the common herbicides used in agriculture. Usage of this herbicide leads to several life-threatening diseases and increases mortality rate. Therefore, quick, selective, and efficient detection of PQ in soil, water, and agro-products is very much essential to prevent its hazardous effects. In this perspective, several methods have been proposed in the literature for the detection of PQ using variety of catalysts.This review provides an insight on the detection of PQ using various analytical techniques including adsorption, spectrophotometric methods, chromatographic methods, and electrochemical methods etc. Further, it focuses on the different type of catalytic materials like metal nanoparticles, carbonaceous materials, and their composites, metals, polymers, and their roles during the determination of PQ. In addition, it analyses the effectiveness of the catalyst materials in terms of sensitivity, selectivity, real time monitoring in fruit juices like potato and apple juices, water samples etc., towards the detection of PQ.